Posterior Chamber Hemorrhage during Fluorescein Angiography - Manuel A. P. Vilela (Case Reports in Ophthalmological Medicine)
This paper provides the first reported case of acute posterior chamber hemorrhage during fluorescein angiography (FA). This is a case review with serial color photographs of the anterior segment. A 76-year-old male was referred for angiographic control of age-related macular degeneration. He was pseudophakic OU, BCVA 20/40 OU. He had mild hypertension, but not diabetes. He had had two previous angiograms without adverse effects. Difficulty was experienced in obtaining the images owing to a progressive reduction in the transparency of the media. A dense hemorrhage in the posterior chamber of the right eye was found, involving the visual axis. Thorough biomicroscopy, gonioscopy, and ultrasonic biomicroscopy showed that part of one of the haptics of the right intraocular lens (IOL) was touching and tearing the posterior face of the iris, without any visible synechiae, iris, or angle neovascularization. Anterior segment FA and posterior ultrasonography were normal. No similar case has been described in the literature involving dense progressive bleeding located in the capsular bag and posterior chamber, without any detectable triggering ocular event other than mydriasis and fluorescein injection. Contact of the iris or sulcus with part of the intraocular lens, aggravated by the intense use of mydriatics during the FA procedure, probably caused bleeding to happen.